2018
DOI: 10.1016/j.healun.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

REVEAL risk score in patients with chronic thromboembolic pulmonary hypertension receiving riociguat

Abstract: Riociguat improved RRS in patients with inoperable and persistent/recurrent CTEPH. RRS at baseline and Week 16, and change in RRS from baseline, predicted survival and clinical worsening-free survival. This analysis of RRS in patients with inoperable or persistent/recurrent CTEPH suggests utility for the RRS in indications beyond PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 29 publications
2
35
0
1
Order By: Relevance
“…However, each of the three abbreviated tools in the current post hoc analysis had the ability to discriminate prognosis for survival and clinical worsening-free survival among patients with inoperable or persistent/recurrent CTEPH following 16 weeks of treatment with riociguat, although further analyses would need to be performed to statistically compare the discriminatory ability of the tools. These observations are in line with similar results found when the RRS was applied to the CHEST study database, in which riociguat significantly improved RRS and risk stratum versus placebo from baseline to week 16 [16]. In addition, RRS at baseline and week 16, and change in RRS during CHEST-1, were significantly associated with survival and clinical worsening-free survival over 2 years in CHEST-2.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, each of the three abbreviated tools in the current post hoc analysis had the ability to discriminate prognosis for survival and clinical worsening-free survival among patients with inoperable or persistent/recurrent CTEPH following 16 weeks of treatment with riociguat, although further analyses would need to be performed to statistically compare the discriminatory ability of the tools. These observations are in line with similar results found when the RRS was applied to the CHEST study database, in which riociguat significantly improved RRS and risk stratum versus placebo from baseline to week 16 [16]. In addition, RRS at baseline and week 16, and change in RRS during CHEST-1, were significantly associated with survival and clinical worsening-free survival over 2 years in CHEST-2.…”
Section: Discussionsupporting
confidence: 88%
“…There is currently no recommendation regarding how to assess risk in patients with inoperable CTEPH; however, in addition to its common and well-validated use in assessing risk in patients with PAH, the REVEAL risk score (RRS) has shown utility as a prognostic tool in patients with CTEPH [16] and a recent study suggested that the Swedish/COMPERA method predicts mortality in non-operated patients with CTEPH [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the first 12 weeks of CHEST-2, this improvement continued in patients who received riociguat in CHEST-1 and former placebo patients who started receiving riociguat in CHEST-2 also demonstrated improvement similar to riociguat patients in CHEST-1. 24 The RRS as well as change in the RRS was shown to be a significant predictor of survival and clinical worsening-free survival over 2-years in CHEST-2. 24 …”
Section: Riociguat For the Treatment Of Ctephmentioning
confidence: 87%
“… 24 The RRS as well as change in the RRS was shown to be a significant predictor of survival and clinical worsening-free survival over 2-years in CHEST-2. 24 …”
Section: Riociguat For the Treatment Of Ctephmentioning
confidence: 87%
“…7,14 The REVEAL risk calculator predicts survival in diverse PAH populations and provides useful serial survival assessments. 7,10,[13][14][15][16][17][18][19][20] More recently, investigators have derived three additional risk assessment strategies using incident patient populations from the Swedish Pulmonary Arterial Hypertension Register (SPAHR), 21 the Comparative, Prospective Registry of Newly Initiated Therapies for Pulmonary Hypertension (COMPERA), 22 and the French Pulmonary Hypertension Registry (FPHR). 23 These risk assessment strategies are made on the basis of thresholds defined by the European Society of Cardiology and European Respiratory Society (ESC/ ERS) 4 in four to eight variables, and are calculated by various methods.…”
mentioning
confidence: 99%